ਫਸਲਾਂ ਵਿਚੋਂ ਨਦੀਨਾਂ ਦੀ ਰੋਕਥਾਮ - Brar, Laal Singh; Valia, Ujagar Singh; Kaur, Baljinder; Bhuller, Sodhak Makhan Singh (Punjab Agricultural University Ludhiana Punjab, 2014)
Measures to remove the harmful weeds in different types of farming is given in this book
Phasalaan Viche Nadinaam Di Rokthaam
Keywords: Punjabi; Agriculture; Punjabi; Punjabi